Some Wheat and Some Chaff: Jean Paulhan and the Postwar Literary Purge in France - Michael Syrotinski (Studies in 20th & 21st Century Literature, 1992)
A somewhat overlooked figure of French literary history, Jean Paulhan has resurfaced in the polemic surrounding the wartime activities of many respected intellectuals, most prominently Blanchot, Heidegger and de Man. Commentators on Paulhan's role in the intellectual history of the period have tended to avoid reading his texts closely. Paulhan—one of the "heroes" of the literary Resistance in France during the Second World War—took the extremely unpopular and controversial stance after the Liberation of criticizing the National Committee of Writers' proposed purge of suspected collaborationist writers. This essay demonstrates the rigorous consistency of Paulhan's position in the context of his other works, and argues for the necessity of taking into account the internal logic and rhetoric, as well as the explicit argument, of his texts. A careful reading of De la paille et du grain (On the Wheat and the Chaff) reveals an unusually forceful and original insight into the relationship between language, literature and political commitment, which has many resonances for current debates on this question.
Keywords: Jean Paulhan; Blanchot; Heidegger; French literary history; intellectuals; Resistance; French literary Resistance; Second World War; WWII; Liberation; National Committee of Writers; rhetoric; De la paille et du grain; On the Wheat and the Chaff; politics; language; literature